Dimensions of Job Satisfaction among Employees of Banking Industry in Nepal - Adhikari, Naba Raj (Journal of Balkumari College, 2020)
Objective: The purpose of the study was to find out the impact of employee empowerment, team work, bank facilities, training; performance appraisal and quality performance upon job satisfaction of employees that how would these factors affect employees’ job satisfaction in banking sector of Nepal. Methodology: Data was collected through questionnaire and the questionnaire was distributed among 200 employees of twenty eight commercial banks. Random sampling technique was applied in this procedure. Correlation coefficient and regression were used to analyze and interpret the data. Results and Conclusion: Regression analysis showed that employee empowerment, team work, and bank facilities affect positively whereas training, performance appraisal and quality performance affect adversely on the job satisfaction level of employees. There exists a positive relation overall and boost job satisfaction, which would in turn enhance the productivity of the organization.